MEMBANGUN KREATIVITAS DIGITAL: PELATIHAN PEMROGRAMAN ARDUINO UNTUK SISWA SDT MUHAMMADIYAH 1 BESUKI - Qodariyah , Nur; Irawan, Dudi; Kurniawati, Lintang Setyo (Jurnal Edukasi Pengabdian Masyarakat, 2025)
SDT Muhammadiyah 1 Besuki, as a partner in community service activities, faces the issue of not yet optimizing the use of technology in learning within the Merdeka Curriculum. The Project for Strengthening the Pancasila Student Profile (P5) with the theme of Engineering and Technology is expected to enable students to optimally utilize and produce products through activities themed around robotics. EdScratch is an excellent and perfect solution for beginner robot developers. Therefore, the aim of this community service activity is to provide robotics training to the students of SDT Muhammadiyah 1 Besuki using the EdScratch application. The activity is conducted using the Training Cycle model. As a result, the robotics training for students at SDT Muhammadiyah 1 Besuki went smoothly. A total of 48.2% of students stated that the training provided met their needs, and 72% of students found the EdScratch application easy to use. About 67.5% of students were able to complete the robot creation stages according to instructions, but only around 33% of students expressed interest in independently developing robots. The robot creation training is very suitable for students in schools implementing the Merdeka Curriculum as it strengthens skills and critical thinking, which are part of the Pancasila Student Profile. Keywords: Independent Curriculum, Strengthening the Pancasila Student Profile, Engineering and Technology, Robotics Skills, EdScratch